2011
DOI: 10.1111/j.1743-6109.2011.02421.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Icariin on Improving Erectile Function in Streptozotocin-Induced Diabetic Rats

Abstract: Introduction Icariin has been shown to improve penile hemodynamics in animal models of erectile dysfunction from cavernous nerve injury and castration. The effects of icariin on penile hemodynamics in diabetic animals remain to be determined. Transforming growth factor β1 (TGFβ1) has been implicated in the pathogenesis of diabetes-related erectile dysfunction. Aim The aim of this study was to investigate the effects of icarii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 27 publications
(34 reference statements)
0
43
0
Order By: Relevance
“…Type 1 diabetic animal models exist: the non-obese diabetic (NOD) mouse, Nethyl-N-nitrosourea diabetes mouse, Goto-Kakizaki (GK) rat, Zuker diabetic fatty (ZDF) rat, and KK-ay mouse (Fenner et al, 2011;Galipeau et al, 2011;Gleeson et al, 2007;Hempe et al, 2011;Hu et al, 2011;Mikai et al, 2010;Yoshinari and Igarashi, 2011;Zhao et al, 2011). The model is induced when either alloxan or streptozotocin is administered to destroy the beta cells, resulting in hyperglycemia (Gohil et al, 2010;Hemalatha et al, 2010;Idan-Feldman et al, 2011;Lee et al, 2011;Liu et al, 2011;Ojezele and Abatan, 2011). Type 2 DM is generally characterized by the body's resistance to insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetic animal models exist: the non-obese diabetic (NOD) mouse, Nethyl-N-nitrosourea diabetes mouse, Goto-Kakizaki (GK) rat, Zuker diabetic fatty (ZDF) rat, and KK-ay mouse (Fenner et al, 2011;Galipeau et al, 2011;Gleeson et al, 2007;Hempe et al, 2011;Hu et al, 2011;Mikai et al, 2010;Yoshinari and Igarashi, 2011;Zhao et al, 2011). The model is induced when either alloxan or streptozotocin is administered to destroy the beta cells, resulting in hyperglycemia (Gohil et al, 2010;Hemalatha et al, 2010;Idan-Feldman et al, 2011;Lee et al, 2011;Liu et al, 2011;Ojezele and Abatan, 2011). Type 2 DM is generally characterized by the body's resistance to insulin.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies have demonstrated that ICA improves cognitive impairments trough different mechanisms in diverse animal models with AD [8][9][10]. It is also reported that ICA is a cGMP-specific PDE 5 inhibitor for the treatment of erectile dysfunction (ED) through stimulation of nitric oxide (NO)/cGMP signaling pathway with selective inhibitory activity on PDE 5 in the penile cavernosum [11][12][13]. Our previous study has shown that ICA improves learning and memory ability in APP/PS1 transgenic mice by stimulating NO/cGMP signaling [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although icariin has been shown to be efficacious in treatment of erectile dysfunction in aged [67], diabetic [68], and castrated [69] animal models, it has not been tested in any randomised clinical trial.…”
Section: Resultsmentioning
confidence: 99%